Contributions to the knowledge of Canuleius Stal (Phasmatodea: Heteronemiidae): taxonomy, morphology and notes on the biology of two species - Crispino, Edgar B.; Chiquetto-Machado, Pedro; Engelking, Phillip W. [UNESP]; Cancello, Eliana M. (Magnolia Press, 2020)
We present new information on the poorly known genus of stick insects, Canuleius Stal, 1875, with redescriptions of two Brazilian species, Canuleius grandis Toledo Piza, 1936 and Canuleius sanguinolentus (Brunner von Wattenwyl, 1907) comb. nov., the latter herein transferred from Bacteria Berthold, 1827. Type material of both species was examined, as well as additional specimens recently collected and deposited at the Museu de Zoologia da Universidade de Sao Paulo (MZUSP). The types of two other species in the genus, Canuleius affinis Toledo Piza, 1936 and Canuleius brevipes Toledo Piza, 1936, were also examined and both species are herein synonymised under C. grandis (syn. nov.). The study includes the first descriptions of the male of C. grandis, the female of C. sanguinolentus and the eggs of both species, which are the first descriptions of eggs of Canuleius. Some notes are presented on the biology of both species, including the first observations of mating and oviposition in Heteronemiidae. Taxonomic aspects of Canuleius are discussed.
Keywords: Stick insect; Pygirhynchini; Atlantic Forest; egg; Bacteria